Hydrogen peroxide electrogeneration in gas diffusion electrode nanostructured with Ta2O5 - Carneiro, Jussara F.; Rocha, Robson S.; Hammer, Peter [UNESP]; Bertazzoli, R.; Lanza, M. R. V. (Elsevier B.V., 2016)
Highly efficient H2O2 electrogeneration is required in the Advanced Oxidation Process for organic wastewater treatment. However, the development of more efficient catalytic particles used in gas diffusion electrodes (GDEs) to enable the oxygen reduction reaction through two-electron transfer is still of great importance. The performance of the Ta2O5 nanoparticles on carbon black in catalyzing the ORR was evaluated using rotating ring-disk electrode. The current efficiency for H2O2 electrogeneration on Ta2O5/C catalyst is 83.2% whereas carbon black exhibits 65.3%. GDEs were constructed using carbon black either unmodified or modified with Ta2O5 nanoparticles. The modified GDE produces 27.9 mg L-1 of H2O2, while the unmodified GDE generates 19.1 mg L-1 of H2O2. Furthermore, the energy consumption for the H2O2 electrogeneration is lower in modified than in unmodified GDE (15.0 kWh vs. 18.8 kWh). The high performance of the GDE (Ta2O5/C) renders it a viable alternative cathode in the electrochemical treatment of wastewaters. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Tantalum oxide; Oxygen reduction reaction; Hydrogen peroxide electrogeneration; Gas diffusion electrode